Contact with out-group friends as a predictor of meta-attitudinal strength and accessibility of attitudes toward gay men. - Vonofakou, C; Hewstone, M; Voci, A (2007)
Two studies examined the effects of cross-group friendships on heterosexuals' attitudes toward gay men. In Study 1, the authors tested the effects of cross-group friendships with gay men on out-group attitudes, meta-attitudinal strength, and attitude accessibility. The authors simultaneously explored mediational effects of intergroup anxiety. Path analysis showed that cross-group friendships were associated with meta-attitudinally stronger and more accessible out-group attitudes, and the effects on all 3 criterion variables were mediated by intergroup anxiety. In Study 2, the authors sought to replicate the basic results of Study 1, while additionally exploring mediational effects of closeness of cross-group friendship and moderational effects of perceived group typicality. Structural equation modeling showed that cross-group friendships were associated with meta-attitudinally stronger and more accessible out-group attitudes; friendships had indirect effects on all 3 criterion variables, via closeness of friendship and intergroup anxiety. Closeness of friendship only predicted lower intergroup anxiety, however, when the out-group friend was perceived as highly typical. The authors emphasize the importance of considering the nature of out-group attitudes more completely when evaluating the effectiveness of intergroup contact in reducing prejudice.